Pengaruh Pad, Dau, Dak Terhadap Pertumbuhan Ekonomi Dengan Belanja Modal Sebagai Variabel Intervening - Pungky Siswiyanti (AKRUAL: JURNAL AKUNTANSI, 2015)
AbstractThe purpose of this study was to determine the effect of PAD, DAU, DAK to Economic Growth with Capital Expenditure as an intervening variable. Data was from the local budget realization report and the GDP report. The study period was during 2012-2014. Analysis of the data used in this study is Path Analysis. The analysis showed the the PAD, DAU positive effect on Economic Growth. While DAK negatively effect to Economic Growth. And the result of the analysis also showed that Capital Expenditure can be used as an intervening variable (mediation) the relationship between PAD and Economic Growth.